ANALISIS DAYA SAING EKSPOR NON MIGAS INDONESIA KE ASEAN - Shanty Oktavilia (Universitas Islam Nahdlatul Ulama Jepara, 2004)
AbstractsThis study analyzes Indonesia's non-oil and gas export in the A SEAN market. Constant Market Share (CMS) method and Trade Specialization Ratio (TSR) are used to analyze competitiveness and specialization of Indonesia's export products based 011 the 2000 2001 data. It is very useful to know the ability of Indonesia's commodity to penetrate and compete in ASEAN market in the AFTA.Based on the CMS method we can decompose the ability to export into growth effect, distribution effect, and competitiveness effect. On average, grow th of Indonesia's export was not affected by market demand growth (negatively sign of growth effect). Only food, beverages and tobacco commodities and livestock have positive sign, that its export growth of those commodities is affected by demand growth. On average, growth of Indonesia's export is affected by market structure (positively sign of distribution effect). It means that Indonesia's export in ASEAN market is concentrated in the growing market . Competitiveness effect shows positive sign on average. It means that Indonesia'. commodities have good competitiveness in ASEAN market. The highest competitiveness are mineral goods, machinery and electronics. Negative sign of distribution effect are showed on Leathe1; leather product, concerning plants, textile, weapon, ammuntion, fabric goods and art. It means that those commodities have low competitiveness.Trade specialization Ratio (TSR) shows how high export goods of Indonesia is specialized in A SEAN market. Indonesia's goods export is getting more specialized from 2000 to 2001 (Showed by increased TSR). Wood products and fabric goods show the highest TSR. Keywords : competitiveness, specialization, constant market share (CMS), trade speciali;:.ation ratio (TSR).